JOB CRAFTING, WORK ENGAGEMENT AND SUSTAINABLE FOR EMPLOYEE PERFORMANCE IN DIRECTORATE OF TELECOMMUNICATIONS DIRECTORAT GENERAL OF POSTAL AND INFORMATICS IMPLEMENTATION IN JAKARTA - Emmywati Emmywati; Noneng R Sukatmadiredja; Bambang Sri Wibowo (Media Mahardhika, 2020)
This study discusses the direct relationship between job crafting, work engagement and sustainable on employee performance at the Telecommunications Directorate of the Directorate General of Postal and Information Technology in Jakarta. job crafting, work engagement and sustainable can be considered as proactive work from work to change their work and work resources to make their work more useful, satisfying, and interesting. job crafting, work engagement and sustainable will have a positive impact on work in a company, one of the impacts is to improve performance, which is one important part of a company. In this study, there were 60 employees and all employees were used as research samples. By using regression analysis, correlation, F-test and T-test. This study shows that employee research is significant with the level of craft work and work results. And employees will truly succeed or survive in the companies that compose them to ensure the safety, health and welfare of their workers. This is evidenced by the results of SPSS calculations which show that the value of the regression coefficient for job crafting (X1) is 0.553, work engagement (X2) is 0.288 and sustainable (X3) is 0.231 meaning that if there is an increase in employee performance (Y) also will increase for X1 is 0.553, X2 is 0.288 and X3 is 0.231. So it can be concluded that the job crafting, work engagement and sustainable will affect the performance of employees in the Telecommunications Directorate at the Directorate General of Postal and Information in Jakarta.